Peningkatan Kompetensi Pedagogik Guru Bahasa Arab Melalui Modul Berbasis HOTS / Increasing the Pedagogical Competency of Arabic Teachers Through HOTS-Based Modules - Rahmawati Rahmawati; Suci Ramadhanti Febriani; Shofia Nailatul Haq (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
Arabic teachers' pedagogical competence in understanding the concept of HOTS-based learning is still minimal. On that basis, increasing teacher pedagogical competence through HOTS-based training aims to encourage teachers to have the capacity to internalize HOTS-based values in the learning process. So, this research aims to identify the increasing teacher pedagogical competence through the Modul based on the HOTS. The service sample consisted of 25 teachers from Limapuluh Kota Regency and Payakumbuh City and the  used a Service Learning (SL) approach for the method. The stages of this activity consist of three parts, namely: 1) The need for pedagogical competence is achieved 100% through the results of discussions and case studies as well as distribution of question instruments on Google Form; 2) the mentoring stage includes steps to analyze KI and KD, formulate learning objectives, prepare research instruments and design HOTS-based modules; 3) while the effectiveness level of this assistance reaches 100%. The impact obtained is increasing insight, establishing good and communicative relationships between Arabic language teachers at Madrasah Aliyah level and the birth of Arabic language teaching modules that can be used in Arabic language learning for the 2023/2024 academic year.Abstrak: Kompetensi pedagogi guru bahasa Arab dalam memahami konsep pembelajaran berbasis HOTS masih minim. Atas dasar itu, peningkatan kompetensi pedagogik guru melalui pelatihan berbasis HOTS bertujuan untuk mendorong guru mempunyai kapasitas internalisasi nilai-nilai berbasis HOTS dalam proses pembelajaran. Maka penelitian ini bertujuan untuk mengidentifikasi peningkatan kompetensi pedagogik guru melalui modul berbasis HOTS. Sampel penelitian ini terdiri dari 25 orang guru Kabupaten Limapuluh Kota dan Kota Payakumbuh dan menggunakan pendekatan Service Learning (SL) sebagai metodenya. Tahapan kegiatan ini terdiri dari tiga bagian, yaitu: 1) kebutuhan kompetensi pedagogik tercapai 100% melalui hasil diskusi dan studi kasus serta pembagian instrumen soal pada Google Form; 2) tahap pendampingan meliputi langkah menganalisis KI dan KD, merumuskan tujuan pembelajaran, menyiapkan instrumen penelitian dan merancang modul berbasis HOTS; 3) sedangkan tingkat efektivitas bantuan ini mencapai 100%. Dampak yang diperoleh adalah bertambahnya wawasan, terjalinnya hubungan yang baik dan komunikatif antar guru bahasa Arab tingkat Madrasah Aliyah dan lahirnya modul pengajaran bahasa Arab yang dapat digunakan dalam pembelajaran bahasa Arab tahun ajaran 2023/2024.